siRNA screening of a targeted library of DNA repair factors in HIV infection reveals a role for base excision repair in HIV integration. - Amy S Espeseth; Rick Fishel; Daria Hazuda; Qian Huang; Min Xu; Kristine Yoder; Honglin Zhou (PLoS ONE)
Host DNA repair enzymes have long been assumed to play a role in HIV replication, and many different DNA repair factors have been associated with HIV. In order to identify DNA repair pathways required for HIV infection, we conducted a targeted siRNA screen using 232 siRNA pools for genes associated with DNA repair. Mapping the genes targeted by effective siRNA pools to well-defined DNA repair pathways revealed that many of the siRNAs targeting enzymes associated with the short patch base excision repair (BER) pathway reduced HIV infection. For six siRNA pools targeting BER enzymes, the negative effect of mRNA knockdown was rescued by expression of the corresponding cDNA, validating the importance of the gene in HIV replication. Additionally, mouse embryo fibroblasts (MEFs) lacking expression of specific BER enzymes had decreased transduction by HIV-based retroviral vectors. Examining the role BER enzymes play in HIV infection suggests a role for the BER pathway in HIV integration.